2,4-Dibromo-6-[(2-hydroxy-5-methylanilino)methylidene]cyclohexa-2,4-dienone - Tarun Kumar Pal; Md Dulal Hossain; Md Chanmiya Sheikh; Ryuta Miyatake; Md Ashraful Alam (IUCrData, 2018)
The new bromo-substituted title compound, C14H11Br2NO2, was synthesized by the condensation of 3,5-dibromosalicylaldehyde and 2-amino-4-methyl phenol. The asymmetric unit consists of two crystallographically independent molecules (A and B), which are related to each other by a pseudo-inversion centre. Both molecules are almost planar; dihedral angles between the two benzene rings are 11.40 (11)° for A and 3.05 (12)° for B. In each molecule, there is an intramolecular N—H...O hydrogen bond with an S(6) ring motif. In the crystal, two independent molecules are linked by O—H...O hydrogen bonds, forming a pseudo-inversion A–B dimer.